2004
DOI: 10.1086/423900
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Scan for Early-Onset Coronary Artery Disease in 438 Families: The GENECARD Study

Abstract: A family history of coronary artery disease (CAD), especially when the disease occurs at a young age, is a potent risk factor for CAD. DNA collection in families in which two or more siblings are affected at an early age allows identification of genetic factors for CAD by linkage analysis. We performed a genomewide scan in 1,168 individuals from 438 families, including 493 affected sibling pairs with documented onset of CAD before 51 years of age in men and before 56 years of age in women. We prospectively def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 47 publications
(74 reference statements)
5
112
0
1
Order By: Relevance
“…Five whole-genome scans for premature MI were identified in PubMed (Helgadottir et al 2004;Wang et al 2004;Broeckel et al 2002;Hauser et al 2004;Samani et al 2005). In these scans, overlapping of cases was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five whole-genome scans for premature MI were identified in PubMed (Helgadottir et al 2004;Wang et al 2004;Broeckel et al 2002;Hauser et al 2004;Samani et al 2005). In these scans, overlapping of cases was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Broeckel et al (2002) consisted of 513 pedigrees with 944 affected individuals (Caucasians); 394 microsatellite markers and multipoint analysis were used. In the study by Hauser et al (2004) the genome scan was performed in 228 pedigrees mainly from a Caucasian population (93%); the number of affected individuals was not reported; the Wang et al (2004) (P values were used). In weighting, the studies by Broeckel et al (2002) and Hauser et al (2004) produced the least weight, with a weight factor w=0.15, and the study by Helgadottir et al (2004), with the most weight (w=0.28).…”
Section: Resultsmentioning
confidence: 99%
“…Although CAD can also rarely be inherited in a Mendelian fashion (predominantly in conditions leading to elevated LDL), this only accounts for a small proportion of incident cases [7], most of which are likely to be polygenic. Linkage studies of non-Mendelian CAD have provided some unbiased associations [8][9][10][11][12][13][14][15][16], even though these have conspicuously lacked reproducibility between cohorts. However, linkage studies will always suffer from poor statistical power and the lack of detailed genomic mapping provided by conventional microsatellite markers.…”
Section: Genome-wide Association Studies: Getting Closer To the Genetmentioning
confidence: 99%
“…In this study, a region on chromosome 14 was linked to the myocardial infarction event; however, the putative causative gene(s) could not be identified further. Another linkage study performed by the Genetics of Early Onset Coronary Artery Diseases (GENECARD) investigators looked at families with early-onset coronary artery disease [10]. In this study, researchers found multiple linked regions on chromosomes 1, 3, 5, 7, and 19, and recently, the GENECARD investigators have identified putative candidate genes within the chromosome 3 regions: the GATA2 transcription factor [11], limbic system-associated membrane protein [12], and Kalirin [13] genes-all of which had never been previously associated with atherosclerosis or CHD.…”
Section: Linkage Analysismentioning
confidence: 99%